Charles Darwin’s Debt to the Romantics - Lansley, Charles Morris (Peter Lang Ltd, 2018)
This book argues that the Romantic movement influenced Charles Darwin and his theory of natural selection. Given that Darwin has traditionally been placed within Victorian naturalism, these Romantic connections have often been overlooked. The volume traces specific examples of Darwin’s reliance on the Romantics – such as Alexander von Humboldt’s Personal Narrative, which he took with him on the Beagle, and the poetry of William Wordsworth, discussed in his notebooks – and explores correlations in Darwin’s own writings. When Darwin refers to the «archetype» in Origin, could he be drawing on Goethe’s own use of the concept? And how to explain his description of all poetry as creating a feeling of «nausea»? In addition to these key figures, the book also explores the possible influence of Darwin’s own grandfather, Erasmus Darwin. The book cleverly follows Darwin’s form of the narrative in a search for traces of history in both science and poetry, inspired by the unique imagination of Darwin himself. «The influence of Charles Darwin’s theory of evolution is famously much-studied; the influences upon Darwin’s theory are less often investigated. Charles Lansley redresses this balance, with regard to Darwin’s debt to the German and English Romantics. This work is by turns delicate and discerning, as appropriate for large-scale and important work of this order.»(Gary Farnell, Senior Lecturer in English, University of Winchester)«This fine study offers a compelling picture of Darwin’s changing relationship to Romanticism during his scientific career. Charles Lansley’s meticulous scholarship and wide-ranging engagement with Darwin’s writings ensure that his account is solidly grounded, yet he also tells a persuasive and engaging story that is never obscured by his detailed research.»(Neil Messer, Professor of Theology, University of Winchester)«This is a persuasive, meticulously researched, and stimulating book that makes a convincing case for Darwin as a 'Romantic' Victorian. In its discussion of Darwin's debt to the Romantics, it acts as a useful reminder of the somewhat arbitrary nature of Romantic and Victorian periodisation. Likewise, it is essential reading for anyone interested in the productive way in which science and art can work together, a topic as germane today as when Darwin first set out, armed with Humboldt's Personal Narrative, on his voyage on the Beagle.» (Jayne Thomas, British Association for Victorian Studies Newsletter, Autumn 2019)...
10.3726/b14594
Keywords: Humboldt; Alexander von; Goethe; Johann Wolfgang von; Wordsworth; William; Darwin; Charles; Rezeption; Evolutionstheorie